Maternal blood lead level and its impact on cord blood hematological parameters - N. T. Gorgadze; Ju. Yu. Ungiadze; L. T. Akhvlediani; D. D. Ungiadze; V. O. Baziari; Kh. N. Lomauri; N. Zh. Kokaia; M. Sh. Giorgobiani (Акушерство, гинекология и репродукция)
Introduction. More than 13 annual million deaths are caused by environmental pollutants worldwide. Urbanization, population growth, industrialization and globalization affect our lives both positively and negatively. Women can become lead exposed through occupational and environmental sources. Once lead enters the body, it is mainly deposited in diverse organs: brain, kidneys, liver and bones. The body stores lead mainly in the bones, where it accumulates over time that may be further released into the bloodstream during pregnancy, thus posing a threat to growing fetus.   Aim: to examine a lead impact on newborn hematological parameters during perinatal period.   Materials and Methods. A retrospective cohort study with 306 pregnant women and paired newborns was carried out. Peripheral blood lead level (BLL) in pregnant and postpartum women was analyzed by using the atomic-absorption spectrophotometry method. Blood specimens were collected for analysis in the third trimester of pregnancy. Newborns hemoglobin concentration (mean corpuscular hemoglobin concentration, MCHC) in erythrocytes was also assessed.   Results. We have detected a statistically significant decrease of MCHC in babies born to mothers with BLL > 0.24 µmol/L vs. BLL < 0.24 µmol/L. This difference may indicate a decline in hemoglobin fetal production caused by lead intoxication.   Conclusion. Study corroborates an idea that pregnant women with occupational or environmental lead exposure should be monitored for BLL, which should not exceed 0.24 µmol/L during pregnancy.